Autorregulación del aprendizaje en logro de competencias del área de desarrollo personal ciudadanía y cívica en estudiantes del primer grado de secundaria del Colegio Nacional Iquitos, distrito de San Juan Bautista 2024 - Del Aguila Santillan, Cristina Elizabeth (2025)
Managing autonomous learning means that students regulate their own learning in order to achieve academic success. Therefore, the objective of this research was to determine the relationship between self-regulation of learning and the achievement of competencies in the area of personal, civic, and citizenship development in 1th grade students at CNI 2024; The methodology used was quantitative, correlational, and cross-sectional, using stratified random sampling of 215 participants. To obtain the results regarding the association of the study variables, Kendall's Tau-b test and Pearson's coefficient were used. These results indicate the level of self-regulation of learning in the achievement of competencies in the area of DPCC, where 44.7% (96) of them presented a good level; 55.6% (113) presented an average level, and 2.8% (6) of them presented a poor level, indicating that as the level of self-regulation of learning increases, there will be an increase in the achievement of competencies in the area of Personal Development, Citizenship, and Civics.